2021
DOI: 10.3390/ijerph18010292
|View full text |Cite
|
Sign up to set email alerts
|

Leading Enterovirus Genotypes Causing Hand, Foot, and Mouth Disease in Guangzhou, China: Relationship with Climate and Vaccination against EV71

Abstract: (1) Background: Assignment of pathogens to the correct genus, species, and type is vital for controlling infectious epidemics. However, the role of different enteroviruses during hand, foot, and mouth disease (HFMD) epidemics and the major contributing factors remain unknown. (2) Methods: HFMD cases from 2016 to 2018 in Guangzhou, China were collected. The relationship between HFMD cases and genotype frequency, as well as the association between genotype frequency and climate factors, were studied using genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…Previous studies found that meteorological factors − including temperature and humidity − can induce EV-A71 and CV-A16 to cause differing epidemic scales. 18 After the launch of the EV-A71 vaccine, the timing of the HFMD epidemic peak was delayed, regardless the serotypes of enterovirus. We think that the increased population immunity created by the EV-A71 vaccination program may disrupt the infection cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that meteorological factors − including temperature and humidity − can induce EV-A71 and CV-A16 to cause differing epidemic scales. 18 After the launch of the EV-A71 vaccine, the timing of the HFMD epidemic peak was delayed, regardless the serotypes of enterovirus. We think that the increased population immunity created by the EV-A71 vaccination program may disrupt the infection cycle.…”
Section: Discussionmentioning
confidence: 99%
“…The two peak patterns were not changed by the introduction of the EN71 vaccine. Climatological factors including temperature and humidity, can induce EV71 and CV-A16 to cause differing epidemic scales [ 25 ]. Lager scales of the autumn peaks were detected in 2018 and 2019 in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Socioeconomic data including gross domestic product (GDP), population density and road network density, were obtained from the Urumqi Statistical Bulletin and Urumqi Statistical Yearbook [26]. Meteorological data, including temperature, precipitation and wind speed, were analyzed [27] from the China Climate Data Sharing Service System (http://data.cma.cn/ (accessed on 2 February 2021) and National Meteorological Information Center [28].…”
Section: Data Acquisitionmentioning
confidence: 99%